Low masses and high redshifts: The evolution of the mass-metallicity relation - Henry, A; Scarlata, C; Domínguez, A; Malkan, M; Martin, C; Siana, B; Atek, H; Bedregal, A; Colbert, J; Rafelski, M; Ross, N; Teplitz, H; et al. (2013)
We present the first robust measurement of the high redshift mass-metallicity (MZ) relation at 108 ≲ M/M ⊙ ≲ 1010, obtained by stacking spectra of 83 emission-line galaxies with secure redshifts between 1.3 ≲ z ≲ 2.3. For these redshifts, infrared grism spectroscopy with the Hubble Space Telescope Wide Field Camera 3 is sensitive to the R 23 metallicity diagnostic: ([O II] λλ3726, 3729 + [O III] λλ4959, 5007)/Hβ. Using spectra stacked in four mass quartiles, we find a MZ relation that declines significantly with decreasing mass, extending from 12+log(O/H) = 8.8 at M = 109.8 M ⊙, to 12+log(O/H) = 8.2 at M = 10 8.2 M ⊙. After correcting for systematic offsets between metallicity indicators, we compare our MZ relation to measurements from the stacked spectra of galaxies with M ≳ 109.5 M ⊙ and z ∼ 2.3. Within the statistical uncertainties, our MZ relation agrees with the z ∼ 2.3 result, particularly since our somewhat higher metallicities (by around 0.1 dex) are qualitatively consistent with the lower mean redshift (z = 1.76) of our sample. For the masses probed by our data, the MZ relation shows a steep slope which is suggestive of feedback from energy-driven winds, and a cosmological downsizing evolution where high mass galaxies reach the local MZ relation at earlier times. In addition, we show that our sample falls on an extrapolation of the star-forming main sequence (the SFR-M * relation) at this redshift. This result indicates that grism emission-line selected samples do not have preferentially high star formation rates (SFRs). Finally, we report no evidence for evolution of the mass-metallicity-SFR plane; our stack-averaged measurements show excellent agreement with the local relation. © 2013. The American Astronomical Society. All rights reserved.